2023
DOI: 10.3390/ijms24087646
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Epimedium Isopentenyl Flavonoids on the Broiler Gut Health Using Microbiomic and Metabolomic Analyses

Abstract: Epimedium (EM), also known as barrenwort, is a traditional medicinal plant rich in isopentenyl flavonols, which have beneficial biological activities and can improve human and animal health, but its mechanism is still unclear. In this study, ultra-high-performance liquid chromatography/quadrupole-time-of-flight-mass spectrometry (UHPLC-Q-TOF/MS) and ultra-high-performance liquid chromatography triple-quadrupole mass spectrometry (UHPLC-QqQ-MS/MS) were used to analyse the main components of EM, and isopentenyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Meanwhile, dietary supplementation with 300 mg/kg CNE increased the levels of serum IgA and IgM. Similarly, Zhang et al [52] found that adding 200 mg/kg of Epimedium Isopentenyl flavonoids to the baseline broiler diet resulted in elevated blood levels of IgA and IgG, accompanied by reduced levels of TNF-α, IL-6, and pro-inflammatory protein IL-1β. NF-κB, considered a crucial downstream mediator in the TLR/MyD88/NF-κB signaling cascade, played a significant role in this process [53], where it was essential for coordinating the expression of adhesion molecules, inflammatory factors, and critical cytokines in vivo [53].…”
Section: Discussionmentioning
confidence: 90%
“…Meanwhile, dietary supplementation with 300 mg/kg CNE increased the levels of serum IgA and IgM. Similarly, Zhang et al [52] found that adding 200 mg/kg of Epimedium Isopentenyl flavonoids to the baseline broiler diet resulted in elevated blood levels of IgA and IgG, accompanied by reduced levels of TNF-α, IL-6, and pro-inflammatory protein IL-1β. NF-κB, considered a crucial downstream mediator in the TLR/MyD88/NF-κB signaling cascade, played a significant role in this process [53], where it was essential for coordinating the expression of adhesion molecules, inflammatory factors, and critical cytokines in vivo [53].…”
Section: Discussionmentioning
confidence: 90%